Retrospective Analysis of 118 Patients With Cutaneous T-Cell Lymphomas: A Single-Center Experience - Polgárová, Kamila; Polívka, Jindřich; Kodet, Ondřej; Klener, Pavel; Trněný, Marek (Frontiers in Oncology, 2022)
Cutaneous T-cell lymphomas (CTCL) represent rare non-Hodgkin lymphomas (NHL) with incidence less than 1 per 100,000 inhabitants. The most common type of CTCL is mycosis fungoides (MF), which represents approx. 60% of all CTCL, followed by Sézary syndrome (SS), approx. 5%. We retrospectively analyzed the outcome of 118 patients with MF (n=96) and SS (n=22) treated between the years 1998 and 2021 at the Charles University General Hospital in Prague, Czech Republic. The ratio between men and women was 1.2:1 (62 men, and 56 women). The median age at diagnosis was 62 years (23 to 92 years). From the MF cohort 48 patients (50% out of MF cohort) presented with advanced stage disease. Ninety patients (77 %) received a systemic treatment at any time from the diagnosis; the median number of therapy lines was two. At the time of database lock, the overall survival (OS) of 96 patients with MF reached 17.7 years with the median follow-up 4.0 years. With the median follow-up 2.6 years, the median OS of 22 patients with SS was 3.5 years. The most common type of systemic therapy for MF included low-dose methotrexate (61%), interferon-alpha (58%), bexarotene (28%), and chlorambucil (25%). The most common type of therapy for SS included bexarotene (64%), extracorporeal photopheresis (50%), and interferon-alpha (45%). Only the minority of patients received innovative targeted agents including brentuximab vedotin, romidepsin, mogamulizumab, or pembrolizumab. Besides the retrospective analysis of the CTCL cohort, current standards and future perspectives of selected innovative agents are summarized and discussed. The analyzed cohort represents the largest cohort of CTCL patients in the Czech Republic. Overall, the survival parameters of our CTCL cohort are comparable to those previously published by other groups. In conclusion, our analysis of a real-world cohort of 118 CTCL patients treated at the single center confirmed the efficacy of immune response modifiers and underlines the urgent need for ample implementation of innovative agents and their combinations into earlier lines of therapy.